Contemporary Development in Western Philosophical Problematization of Evil: A Contextualized Overview - Wan Abdullah, Wan Suhaimi; Hamdan, Mohamad Fahroni (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
Western philosophical study of religion, particularly by the analytic philosophers in contemporary times, has raised many issues about religious truth in reference to theism. One of the major issues is their problematization of evil, which they treated as logical and evidential arguments against the existence of theistic God. With the consideration of being neutral and objective, their treatment of the problem assumes a dialectical relevance for the theists, including the Muslims, to respond in two customarily ways of either theodicy or defense. However, a question should rather be raised, at least by the discerning Muslims, on to what extent their philosophical formulation and establishment of the problem is relevant to religions other than Western Christianity. This article aims to articulate a contextualized overview of contemporary development in the philosophical problematization of evil especially the ones developed in the analytical discourse. This contextualization is crucial to adjudicate that their treatment of the problem, in its essence, reflects more of the religio-philosophical experience and consciousness of Western man, hence, diluting at once their claim for neutrality and objectivity.